Wybrane elementy oceny gospodarki paszowej w gospodarstwach rolniczych - Szymańska, Elżbieta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2000)
The major objective of this study was to evaluate the fodder economy in agricultural holdings classified according to production types. The data was derived from the sample of 334 investigated agricultural holdings with animal production. An analysis was conducted on the basis of the results obtained by these holdings in 1996. To assess the fodder economy, the following indicators were applied: the structure of fodder acreage, the fodder plants yields, the efficiency of fodder area utilisation, the level of fodder inputs and their structure. Results from the study indicate that it was an arable land that constituted the main supply basis for animal fodder. Nevertheless, the noted level of fodder crops output suggests that there exists an opportunity to intensify the utilisation of the fodder area in the investigated farms. The highest level of animal output per 1 ha of fodder area was reached in pig farms, the lowest one respectively in crop farms. Additionally, the research outcomes show that the fodder applications for animals were not balanced in the investigated farms.